Menara Tabung Haji Ipoh / Nicholas Egat Menari... [et al.] - Menari, Nicholas Egat; Jawal, Mohd Azlan; Musi, Mohd Redzuan; Rozali, Nursyuhada; Yahya@Yahaya, Nurul Ain (Universiti Teknologi Mara, Perak, 2017)
In this case study that we have given a task for doing the inspection work at our site . For our study case we had choose requirement number three that it was medium rise buildings (6 storeys and above such as office building , institution building , hotel or etc.), and shall be built in 2005 and above , equipped with advanced technology with minimum 2 years operation . Besides that , for the building background is to describe in detail the background of the property or case study . The study shall covers the address of the property , location plan that explain on where the building can be found on the map , building adjacent , year of built , year of completion , contract sum , building function , building history (any maintenance information record such as renovation , refurbishment) , building details (no. of storey or building size) , photos for various view .